Prevalence of Intestinal Parasites among Children in Khanaqin City East of Diyala/Iraq (Medico Legal Update, 2020)
The current study was carried out during the period between November/2018 and March/2019. The studywas aiming to investigate the types and proportions of intestinal parasites among children who visited theprimary health care center in the city of Khanaqin - Diyala governorate. The total number of specimensexamined, during the course of study, was 805 stool specimens. These specimens were taken from childrenin the age range 1-10 years, and direct smear was the method used for the investigation of the intestinalparasites existence. The results showed that 156 children were infected with intestinal parasitic infections.These infections were categorized as four types of Protozoa and one type of intestinal Helminthes. Theincidence ratio of intestinal parasitic infection was 19.373%, where the percentages of parasites consideredin the current study have found to be 62.179% for the Entamoebahistolytica followed by 12.820% for theGiardia lamblia, 12.820 of Entamoebacoli, and 3.205% for the Iodomoebabutschillii. Moreover, the studyhas reported one type of Helminthes represented by the Entrobiusvermicularis with occurrence ratio of6.410%.